Determinants of Parents' Decision to Choose Private Junior School - Djazilan, Sukron; Retnowati, Eli; Masnawati, Eli; Mardikaningsih, Rahayu; Darmawan, Didit (International Journal of Elementary Education, 2023)
Every parent prepares their children's future by providing a good education. Parents often choose private junior high schools over public ones because they are thought to provide a better education. It is driven by various factors ranging from teachers, the quality of school services, learning facilities, and the parents' social environment. This research aims to analyze the factors driving parents' decisions to choose private junior high schools. This type of research is quantitative. This research used 100 samples obtained through the purposive sampling technique. The research sample was parents who entrusted private junior high schools as their children's educational institutions. The data collection method uses a questionnaire. The data collection instrument uses a questionnaire sheet. The technique used to analyze data is inferential statistics. Research data was analyzed using multiple linear regression. The research results show that teacher quality significantly influences parents' decisions in choosing private junior high schools. This research also proves that there is a significant influence of service quality on parents' decisions to choose private junior high schools. Learning facilities have been proven to significantly influence parents' decisions to choose private junior high schools. Furthermore, this research also proves that the social environment influences parents to choose private junior high schools.